Exploring growth, maturity, and age as injury risk factors in high-level youth football - Wik, E. H.; Chamari, K.; Tabben, M.; Di Salvo, V.; Gregson, W.; Bahr, R. (Sports Medicine International Open, 2024)
Rapid somatic growth and biological maturity status may affect injury patterns in youth football, yet firm conclusions cannot be drawn from the existing research. We aimed to explore growth velocity, maturity, and age as injury risk factors in 95 academy players (11.9-15.0 years), using anthropometric (height and body mass), maturity (skeletal age), injury, and football exposure data collected prospectively over three seasons (2016/17-2018/19). We compared the relative quality of mixed-effects logistic regression models with growth velocity for 223 growth intervals (average 113 days) included as fixed effects and adjusted for age (chronological or skeletal) plus load (hours/week). Associations were considered practically relevant based on the confidence interval for odds ratios, using thresholds of 0.90 and 1.11 to define small beneficial and harmful effects, respectively. We observed harmful effects of older age on overall (OR: 2.61, 95% CI: 1.15-5.91) and sudden onset (1.98, 1.17-3.37) injury risk. Significant associations (p<0.05) were observed for higher body mass change and greater maturity on sudden onset injuries, and for higher hours/week on gradual onset, bone tissue, and physis injuries. Future studies should include larger samples, monitoring athletes from pre-adolescence through maturation, to enable within-subject analyses and better understand the relationship between growth, maturation, and injuries.